IMPLEMENTASI MODEL PEMBELAJARAN BERDIFERENSIASI DALAM MENINGKATKAN EFEKTIVITAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM: KAJIAN LITERATUR - Rohana, Sy. (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
Islamic Religious Education (PAI) faces challenges in accommodating the diverse characteristics of students, including differences in learning readiness, interests, learning styles, and socio-cultural backgrounds. One relevant approach to addressing these challenges is the differentiated learning model. This article aims to conceptually analyze the implementation of differentiated learning in Islamic Religious Education, including its fundamental concepts, characteristics, implementation procedures, and challenges encountered in practice. This study employs a library research method by collecting and analyzing various scholarly sources such as books, journal articles, and educational policy documents related to differentiated instruction and Islamic Religious Education. The findings indicate that differentiated learning enables teachers to adjust content, learning processes, and learning products according to students’ needs, thereby creating a more inclusive, effective, and meaningful learning environment. The implementation of this model contributes to increased motivation, active participation, and the development of students’ cognitive, affective, and psychomotor domains. Therefore, differentiated learning serves as an essential strategy in supporting the optimal and sustainable achievement of Islamic Religious Education learning objectives. ABSTRAK Pembelajaran Pendidikan Agama Islam (PAI) menghadapi tantangan dalam mengakomodasi keberagaman karakteristik peserta didik yang meliputi perbedaan kesiapan belajar, minat, gaya belajar, serta latar belakang sosial dan kultural. Salah satu pendekatan yang relevan untuk menjawab tantangan tersebut adalah model pembelajaran berdiferensiasi. Artikel ini bertujuan untuk menganalisis secara konseptual penerapan model pembelajaran berdiferensiasi dalam pembelajaran PAI, meliputi konsep dasar, karakteristik, langkah-langkah implementasi, serta kendala yang dihadapi dalam praktiknya. Penelitian ini menggunakan metode kajian pustaka (library research) dengan mengumpulkan dan menganalisis berbagai sumber ilmiah berupa buku, artikel jurnal, dan dokumen kebijakan pendidikan yang berkaitan dengan pembelajaran berdiferensiasi dan PAI. Hasil kajian menunjukkan bahwa pembelajaran berdiferensiasi memungkinkan guru menyesuaikan konten, proses, dan produk pembelajaran sesuai kebutuhan peserta didik, sehingga tercipta pembelajaran yang lebih inklusif, efektif, dan bermakna. Penerapan model ini berkontribusi terhadap peningkatan motivasi, partisipasi aktif, serta pengembangan aspek kognitif, afektif, dan psikomotorik peserta didik. Dengan demikian, pembelajaran berdiferensiasi menjadi strategi penting dalam mendukung pencapaian tujuan pembelajaran PAI secara optimal dan berkelanjutan.